Diosmetin inhibits osteoclast formation and differentiation and prevents LPS‐induced osteolysis in mice. Issue 8 (4th December 2018) - Shao, Siyuan; Fu, Fangsheng; Wang, Ziyi; Song, Fangming; Li, Chen; Wu, Zuo‐xing; Ding, Jiaxing; Li, Kai; Xiao, Yu; Su, Yiji; Lin, Xixi; Yuan, Guixin; et al.
Abstract: Osteolytic bone diseases are closely linked to the over‐activation of osteoclasts and enhancement of bone resorption. It has become a major health issue in orthopedic practice worldwide. Inhibition of osteoclasts is proposed to be the main treatment for osteolytic disorders. Diosmetin (DIO) is a natural flavonoid with properties of antioxidant, anti‐infection, and antishock. The effect of DIO on osteoclast differentiation is poorly understood. In this study project, we found that DIO could inhibit osteoclastic formation induced by receptor activator of nuclear factor kappa‐B ligand (RANKL) in a dose‐dependent manner. The expression of the osteoclast differentiation marker genes, cathepsin K, nuclear factor of activated T‐cells 1 ( NFATc1 ), Acp5, Ctr, Atp6v0d2, and Mmp9 were also decreased by the treatment of DIO. In addition, DIO attenuated the formation of actin ring and the ability of bone resorption. Further, the western blotting showed that DIO inhibits the phosphorylation of the mitogen‐activated protein kinases signaling pathway induced by RANKL, accompanied by the downregulation of NFATc1 and c‐Fos expression. We also found that DIO could reduce the accumulation of reactive oxygen species (ROS) induced by RANKL. In vivo, the study revealed that DIO can significantly reduce LPS‐induced osteolysis in mice. Collectively, our study shows that DIO can inhibit osteoclast formation and activation, and could serve as a potential therapeutic drug for osteolytic bone diseases. Abstract : In summary, our study has demonstrated for the first time that DIO has the capacity of diminishing osteoclast differentiation and osteoclast resorption activity, mainly by inhibiting the MAPK signaling pathway, rather than the NF‐κB signaling pathway